TELAAH FUNGSI MAKNA LOGIS PADA CERITA RAKYAT TIMUN EMAS DAN TERJEMAHANNYA - Dimas Adika (Prasasti: Journal of Linguistics)
This article discusses the function of logical meaning which can be identified from logico-semantic and taxis interdependence. This descriptive-qualitative research employs systemic functional linguistics approach. The data sources are all clause complexes in the Timun Emas folkflore written by the best IKAPI writer and translated into English by the translator of Litte Serambi. The function of logical meaning (projection, enhancement and extension) in source and target language spreads to all text structures, started from orientation, complication, evaluation, resolution and coda. The complication had distinctive feature of projection showed by dialogues between characters. Temporal series in the enhancement (time) plays pivotal role in constructing events. Then, the the extension function in Timun Emas folklore and its translation is worthwhile to give information for the comprehensible narrative with the help of chronological series from enhancement (time) function.Next, some changes of the logical meaning after translation process do not seemingly influence to the text structure of this folklore.